Spatial and temporal trends in order richness of marine phytoplankton as a tracer for the exchange zone between coastal and open waters. (20th October 2016) - Jung, A.S.; Bijkerk, R.; Van Der Veer, H.W.; Philippart, C.J.M.
Abstract : Quantifying exchange of particulate matter between coastal and open waters is an important and often unresolved issue. Here, we apply phytoplankton order richness as an innovative marine tracer to identify the geographic position of a coastal exchange zone in the SE North Sea, including its variability in time and space. Previous observations on dynamics of suspended particulate matter accumulation resulted in a hypothesized boundary between coastal waters (including the Wadden Sea) and open North Sea waters, the so-called 'line-of-no-return'. Our study along two transects (Terschelling, Noordwijk) in the Dutch coastal zone showed seasonality patterns in phytoplankton order richness, both for diatoms and flagellates. The coastal Wadden Sea was found to be clearly different from the open North Sea, implying that seasonality in Wadden Sea phytoplankton is at least partly driven by local environmental conditions. Seasonality in flagellates was found to be more uniform than seasonality in diatoms. Stations in the coastal North Sea to a distance of 10 km (Terschelling) to 20 km (Noordwijk) from the shore appeared to be at the inside of the 'line-of-no-return'. Our findings indicate that this approach is a useful aid in exploring mixing of particulate matter between coastal and open waters and to study the responses of phytoplankton communities to environmental drivers.